Resin particles, conductive particles, conductive material, and connection structure
By performing specific compression treatment on the resin particles and forming conductive parts on the surface, combining conductive particles with binder resin, the problem of insufficient deformation of conductive particles and difficult to increase the contact area of resin particles is solved, and efficient electrical connection and conduction reliability is achieved.
Patent Information
- Application Number
- CN202080056492.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-12
- Filing Date
- 2020-08-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-08-06
AI Technical Summary
The existing conductive particles may not be sufficiently deformed during conductive connection between electrodes or compressed conductive particles attempt to restore their original shape, resulting in insufficient contact area or interface peeling, increasing connection resistance and reducing conduction reliability. At the same time, the contact area and friction resistance of resin particles are difficult to fully increase when used as spacers, resulting in difficulty in interface peeling and thickness control.
By compressing the resin particles 30% of the particle size and holding it at 200° C. for 10 minutes, the compression is relieved, so that the distance between one end and the other end in the compression direction is X, so as to ensure that the length-to-diameter ratio of the resin particles after compression is relieved is 0.60 or more and 0.95 or less. Meanwhile, a conductive portion is formed on the surface of the resin particles, and conductive particles are formed, and bonded to the adhesive resin to form a conductive material to achieve electrical connection.
By increasing the contact area and friction resistance between the resin particles or particles using resin particles and the attached body, interface peeling is suppressed, the contact area between the conductive particles and the electrode is improved, the connection resistance is reduced, the conduction reliability is enhanced, and stability can be maintained under high temperature and high humidity conditions.
Smart Images

Figure CN114207025B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to resin particles having good compression characteristics and also to conductive particles, conductive materials and bonded structures using the resin particles. Background Art
[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known. In the anisotropic conductive materials, conductive particles are dispersed in a binder.
[0003] The anisotropic conductive material is used to electrically connect electrodes of various connection target components such as flexible printed circuit boards (FPCs), glass substrates, glass epoxy substrates, and semiconductor chips to obtain a connection structure. In addition, as the conductive particles, conductive particles having resin particles and conductive portions disposed on the surfaces of the resin particles may be used.
[0004] In addition, a liquid crystal display element is formed by disposing liquid crystal between two glass substrates. In order to keep the gap between the two glass substrates uniform and fixed, a spacer is used as a gap control material. As the spacer, resin particles are generally used.
[0005] In the following patent document 1, a photosensitive composition for color filters is disclosed, which contains at least the following (A), (B), and (C): a resin (A) containing an acidic group and a group having an ethylenically unsaturated bond on the side chain; a polymerizable compound (B) containing two or more polymerizable substituents having an ethylenically unsaturated bond and a divalent or higher group containing a ring structure bonded to the polymerizable substituent; and a photopolymerization initiator (C). In patent document 1, it is described that the photosensitive composition preferably contains microparticles (D), and that PS (photo spacer) can be formed using the photosensitive composition. In the examples of patent document 1, the deformation recovery rate of PS formed by the photosensitive composition is evaluated, but it is only described that the deformation recovery rate is preferably high.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-162871 Summary of the invention
[0009] Technical Problems to be Solved by the Invention
[0010] In the case of conventional conductive particles, when the electrodes are electrically connected, the conductive particles are not fully deformed, or the compressed conductive particles try to restore their original shape. In this case, the contact area between the conductive particles and the electrode (attachment) cannot be fully enlarged, or the interface between the conductive particles and the electrode is peeled off, the connection resistance increases, and the conduction reliability decreases.
[0011] In addition, when conventional resin particles are used as spacers, the contact area and friction resistance between the resin particles and the connection object part (attachment) cannot be sufficiently increased, and the resin particles cannot be fixed at a given position due to tumbling, etc. In this case, peeling occurs at the interface between the resin particles and the connection object part, and the thickness between the connection object parts cannot be uniformly controlled, and the function as a spacer cannot be fully exerted.
[0012] The object of the present invention is to provide a resin particle that can increase the contact area and friction resistance between a resin particle or a particle using the resin particle and an adherend, thereby suppressing interface peeling between the resin particle or a particle using the resin particle and an adherend. In addition, the object of the present invention is to provide a conductive particle, a conductive material, and a connection structure using the resin particle.
[0013] Technical means to solve technical problems
[0014] According to a broad scheme of the present invention, a resin particle is provided, wherein the resin particle is kept at 200°C for 10 minutes in a state where the particle diameter is compressed by 30%, and then the compression is released, and the distance between one end and the other end of the resin particle in the compression direction after the compression is released is set to X. At this time, the ratio of the major diameter of the resin particle after the compression is released at a position of 0.05X from the one end toward the other end to the major diameter of the resin particle after the compression is released at a position of 0.5X from the one end toward the other end is greater than 0.60 and less than 0.95.
[0015] In a specific embodiment of the resin particles according to the present invention, the thermal decomposition temperature is 200° C. or higher and 350° C. or lower.
[0016] In a specific embodiment of the resin particles according to the present invention, the compression modulus when compressed by 10% is 100 N / mm 2 Above 3500N / mm 2 the following.
[0017] In a specific embodiment of the resin particles according to the present invention, the compression modulus when compressed by 30% is 100 N / mm 2 Above 3000N / mm 2 the following.
[0018] In a specific embodiment of the resin particle according to the present invention, the resin particle is used for a spacer, for an adhesive for electronic components, for obtaining conductive particles having a conductive portion, or for a laminate forming material.
[0019] In a specific aspect of the resin particle according to the present invention, the resin particle is used as a spacer for a liquid crystal display element, as an adhesive for an electronic component, or for obtaining conductive particles having a conductive portion.
[0020] According to a broad aspect of the present invention, there is provided a conductive particle including the above-mentioned resin particle and a conductive portion disposed on a surface of the resin particle.
[0021] In a specific aspect of the conductive particle according to the present invention, the conductive particle further includes an insulating substance disposed on the outer surface of the conductive portion.
[0022] In a specific aspect of the conductive particle according to the present invention, the conductive particle has a protrusion on an outer surface of the conductive portion.
[0023] According to a broad aspect of the present invention, there is provided a conductive material including conductive particles and a binder resin, wherein the conductive particles include the above-mentioned resin particles and a conductive portion disposed on a surface of the resin particles.
[0024] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection object member, a second connection object member, and a connection portion connecting the first connection object member and the second connection object member, wherein the connection portion is formed of the above-mentioned resin particles or a composition containing the resin particles.
[0025] According to a broad scheme of the present invention, there is provided a connection structure comprising a first connection object component having a first electrode on its surface, a second connection object component having a second electrode on its surface, and a connection portion connecting the first connection object component and the second connection object component, wherein the connection portion is formed by conductive particles, or is formed by a conductive material comprising the conductive particles and a binder resin, the conductive particles comprising the above-mentioned resin particles, and a conductive portion arranged on the surface of the resin particles, and the first electrode and the second electrode are electrically connected via the conductive particles.
[0026] Effects of the Invention
[0027] With respect to the resin particles involved in the present invention, after the resin particles are kept at 200°C for 10 minutes in a state where the particle diameter is compressed by 30%, the compression is released, and the distance between one end and the other end of the resin particles in the compression direction after the compression is released is set to X. With respect to the resin particles involved in the present invention, the ratio of the major axis of the resin particles after the compression is released at a position of 0.05X from the one end toward the other end to the major axis of the resin particles after the compression is released at a position of 0.5X from the one end toward the other end is greater than 0.60 and less than 0.95. With respect to the resin particles involved in the present invention, since they have the above-mentioned structure, the contact area and friction resistance between the resin particles or the particles using the resin particles and the adherend can be increased, so that the interface peeling between the resin particles or the particles using the resin particles and the adherend can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] [ Figure 1 ] Figure 1 This is a cross-sectional view showing a resin particle according to a first embodiment of the present invention. Figure 1 (a) is a cross-sectional view showing a resin particle before compression, Figure 1 (b) is a cross-sectional view showing the resin particle after the compression is released.
[0029] [ Figure 2 ] Figure 2 It is a cross-sectional view which shows the electroconductive particle which concerns on 1st Embodiment of this invention.
[0030] [ Figure 3 ] Figure 3 It is a cross-sectional view showing the conductive particles according to the second embodiment of the present invention.
[0031] [ Figure 4 ] Figure 4 It is a cross-sectional view showing the conductive particles according to the third embodiment of the present invention.
[0032] [ Figure 5 ] Figure 5 This is a cross-sectional view showing an example of a connection structure using the conductive particles according to the first embodiment of the present invention.
[0033] [ Figure 6 ] Figure 6 This is a cross-sectional view showing an example of an electronic component device using the resin particles according to the present invention.
[0034] [ Figure 7 ] Figure 7 For the general Figure 6 The electronic component device shown is a partially enlarged cross-sectional view of a joint portion.
[0035] [ Figure 8 ] Figure 8 (a) is a representative electron microscope photograph of resin particles (resin particles before thermal curing). Figure 8 (b) is a representative electron micrograph of the resin particles after the compression is released.
[0036] [ Fig. 9 ] Fig. 9 This is an electron microscope photograph of the resin particles in Example 8 after the compression was released.
[0037] [ Fig.10 ] Fig.10 (a) is an electron microscope photograph of the resin particles after the compression was released in Comparative Example 1, Fig.10 (b) is an electron microscope photograph of the resin particles after the compression was released in Comparative Example 2, Fig.10 (c) is an electron micrograph of the resin particles in Comparative Example 3 after the compression was released.
[0038] Specific embodiments of the present invention
[0039] Hereinafter, the details of the present invention will be described.
[0040] (resin particles)
[0041] The resin particles according to the present invention are held at 200° C. for 10 minutes in a state where the particle diameter is compressed by 30%, and then the compression is released, and the distance between one end and the other end of the resin particles in the compression direction after the compression is released is set to X. The resin particles according to the present invention have a ratio of the major diameter of the resin particles after the compression is released at a position of 0.05X from the one end toward the other end to the major diameter of the resin particles after the compression is released at a position of 0.5X from the one end toward the other end of 0.60 or more and 0.95 or less.
[0042] The resin particles according to the present invention have the above-mentioned structure, so that the contact area and friction resistance between the resin particles or particles using the resin particles and the adherend can be increased, thereby suppressing interface peeling between the resin particles or particles using the resin particles and the adherend.
[0043] The resin particles of the present invention can be heat-cured by heating. The resin particles of the present invention can be heat-cured by heating. The resin particles of the present invention (resin particles before heat curing) are not completely heat-cured, and can well maintain the compressed shape when heated and compressed. Whether the resin particles of the present invention can be heat-cured can be confirmed as follows.
[0044] After heating the resin particles before thermal curing at 200°C for 1 hour, cool them at 25°C for 1 hour. Based on the compression modulus (10% K value) when the heated and cooled resin particles are compressed by 10% and the compression modulus (10% K value) when the resin particles before thermal curing are compressed by 10%, the change rate of the compression modulus before and after thermal curing is calculated by the following formula. If the change rate of the modulus before and after thermal curing calculated by the following formula is 105% or more, it is considered that thermal curing caused by heating occurs, and the particles are regarded as being capable of thermal curing by heating. It should be noted that the 10% K value of the resin particles can be measured by the method described later.
[0045] Change rate of compression modulus before and after thermal curing (%) = (10% K value of resin particles after heating and cooling) / (10% K value of resin particles before thermal curing) × 100
[0046] If the resin particles of the present invention are used in the form of conductive particles having a conductive portion formed on the surface of the resin particles, the conductive particles are deformed well during the thermocompression bonding of the conductive particles and the electrode (attached body), and the compressed shape is maintained after the thermocompression bonding, so the contact area between the conductive particles and the electrode can be increased. Therefore, the interface peeling between the conductive particles and the electrode can be suppressed, and the damage to the electrode can be effectively suppressed. In addition, when the electrodes are electrically connected, the adhesion between the resin particles in the conductive particles and the conductive portion can be improved. Therefore, with respect to the conductive particles using the resin particles of the present invention, the connection resistance of the connection structure that electrically connects the electrodes through the conductive particles can be effectively reduced, and the conduction reliability can be improved. In addition, even if the connection structure is placed for a long time under high temperature and high humidity conditions, the connection resistance is not easy to increase, and poor conduction is not easy to occur. Moreover, even if the connection structure is impacted by falling, the interface peeling between the conductive particles and the electrode can be suppressed.
[0047] In addition, when the resin particles of the present invention are used as spacers (spacer materials) or adhesives for electronic parts, the resin particles are deformed well when the resin particles and the connection object parts (attached body) are hot-pressed, and the compressed shape is maintained after hot-pressing, so the contact area and friction resistance between the resin particles and the connection object parts can be increased, and the resin particles are easily fixed at a given position. Therefore, with regard to the spacers or adhesives for electronic parts using the resin particles of the present invention, the interface peeling between the resin particles and the connection object parts can be suppressed. With regard to the spacers or adhesives for electronic parts using the resin particles of the present invention, the thickness between the connection object parts can be uniformly controlled.
[0048] The resin particles according to the present invention are held at 200° C. for 10 minutes in a state where the particle diameter is compressed by 30%, and then the compression is released, and the distance between one end and the other end of the resin particles in the compression direction after the compression is released is set to X. The resin particles according to the present invention have a ratio of the major diameter of the resin particles after the compression is released at a position of 0.05X from the one end toward the other end to the major diameter of the resin particles after the compression is released at a position of 0.5X from the one end toward the other end of 0.60 or more and 0.95 or less. The resin particles according to the present invention have compression characteristics different from those of conventional resin particles.
[0049] The compression of the resin particles and the observation of the resin particles after the compression was released were specifically performed as follows.
[0050] Prepare the first plate and the second plate. The first plate and the second plate each have a flat surface. At the end of the surface of the first plate or the second plate, a polyimide film having a thickness of 70% of the particle size of the resin particles is attached as a spacer. Heat the first plate and the second plate so that the surface temperature is 200°C. Arrange the resin particles on the surface of the heated first plate. Use a Vice Heat Press Machine Digital (for example, "MNP2-002D" manufactured by AS ONE) to move the first plate or the second plate to a position where the distance between the first plate and the second plate is 70% of the particle size of the resin particles. That is, the resin particles are compressed by 30% in terms of particle size. Compress the resin particles with the flat portions of the first plate and the second plate. The compression conditions are set to a compression speed of 2000mN / sec and a load of 20000mN. The resin particles were compressed by 30%, held at 200°C for 10 minutes under a load of 20,000 mN, and then released. The released resin particles were left at 25°C for 1 hour in a windless condition, and then photographed with an electron microscope or an optical microscope to observe the shape of the resin particles.
[0051] The material of the first plate and the second plate is preferably glass, stainless steel (SUS) or silicon, and more preferably glass.
[0052] The particle size of the resin particles is preferably an average particle size, preferably a number average particle size. It should be noted that the method for measuring the particle size of the resin particles is described below.
[0053] From the viewpoint of exerting the effect of the present invention, the ratio of the major diameter (A) of the resin particle after the compression is released at a position of 0.05X from the one end toward the other end to the major diameter (B) of the resin particle after the compression is released at a position of 0.5X from the one end toward the other end (major diameter (A) / major diameter (B)) is greater than 0.60 and less than 0.95.
[0054] From the viewpoint of further effectively exerting the effect of the present invention, the ratio (major diameter (A) / major diameter (B)) is preferably 0.65 or more, preferably 0.90 or less, more preferably 0.85 or less, and further preferably 0.80 or less. The ratio (major diameter (A) / major diameter (B)) is preferably obtained by observing 50 arbitrary resin particles with an electron microscope or an optical microscope and calculating the average value of the ratio (major diameter (A) / major diameter (B)) of each resin particle.
[0055] As a method for making the ratio (long diameter (A) / long diameter (B)) satisfy the above range, for example, a method of using resin particles having flexibility and low resilience can be cited. As a method for obtaining resin particles having flexibility and low resilience, for example, a method of lowering the reaction temperature when the resin particles are produced can be cited. More specifically, a method of using a thermosetting resin as a material for the resin particles and suppressing the reaction temperature to below 80°C (preferably below 70°C) can be cited.
[0056] The resin particles may be used without being heated at 200° C. or compressed by 30%, for example. The compression of the resin particles and observation of the resin particles after compression release are performed to evaluate the compression characteristics of the resin particles.
[0057] Figure 1 It is a cross-sectional view showing the resin particles according to the first embodiment of the present invention. Figure 1 (a) is a cross-sectional view showing a resin particle before compression, Figure 1 (b) is a cross-sectional view showing the resin particles after the compression is released. Figure 8 (a) is a representative electron micrograph of resin particles (resin particles before thermal curing). Figure 8 (b) is a representative electron micrograph of resin particles after compression release.
[0058] Figure 1 The shape of the resin particle 1 before compression shown in (a) is spherical. Figure 1 The resin particles 1 after the compression is released shown in (b) are Figure 1The resin particles 1 shown in (a) are obtained by holding the particles at 200° C. for 10 minutes in a state where the particle diameter is compressed by 30%, and then releasing the compression. Figure 1 The resin particle 1 after compression release shown in (b) has one end and the other end in the compression direction P. The resin particle 1 after compression release has a first surface 1a at the one end and a second surface 1b at the other end. The first surface 1a and the second surface 1b are planar portions facing each other. The first surface 1a and the second surface 1b are formed from the surfaces of the first plate and the second plate used when the resin particle 1 is compressed by 30%. The first surface 1a and the second surface 1b are planes. The shapes of the first surface 1a and the second surface 1b are circular.
[0059] The distance between the one end and the other end is X. The major diameter of the resin particle after compression release at a position of 0.05X from the one end toward the other end is A. The major diameter of the resin particle after compression release at a position of 0.5X from the one end toward the other end is B. The ratio of the major diameter (A) to the major diameter (B) of the resin particle 1 after compression release (major diameter (A) / major diameter (B)) is greater than 0.60 and less than 0.95. For example, the major diameter (A) and the major diameter (B) of the resin particle after compression release can be calculated by observing the resin particle after compression release from a direction perpendicular to the compression direction. At this time, for the major diameter (A) and the major diameter (B) of the resin particle after compression release, it is preferred to use the resin particles observed at an angle within ±15° in the compression direction relative to the direction perpendicular to the compression direction among the observed resin particles.
[0060] The resin particles after the compression is released may not have two planar portions facing each other in the compression direction.
[0061] The aspect ratio of the resin particles (before compression) is preferably 2 or less, more preferably 1.5 or less, and further preferably 1.2 or less. The aspect ratio of the resin particles (before compression) represents the major diameter / minor diameter. The aspect ratio of the resin particles (before compression) is preferably obtained by observing any 50 resin particles with an electron microscope or an optical microscope, setting the maximum diameter and the minimum diameter as the major diameter and the minor diameter, respectively, and calculating the average value of the major diameter / minor diameter of each resin particle.
[0062] The aspect ratio of the resin particles after compression is released, as viewed from a direction perpendicular to the compression direction, generally exceeds 1. The aspect ratio of the resin particles after compression is released, as viewed from a direction perpendicular to the compression direction, may be greater than 1.1, may be greater than 1.3, may be less than 5, may be less than 3, may be less than 2, or may be less than 1.5. The aspect ratio of the resin particles after compression is released represents the major axis / minor axis of the resin particles as viewed from a direction perpendicular to the compression direction. The aspect ratio of the resin particles after compression is released is preferably obtained by observing any 50 resin particles with an electron microscope or an optical microscope, setting the maximum diameter and the minimum diameter of the resin particles as viewed from a direction perpendicular to the compression direction as the major axis and the minor axis, respectively, and calculating the average value of the major axis / minor axis of each resin particle. For example, Figure 1 For the resin particle 1 after compression release shown in (b), the aspect ratio is the ratio of the longest diameter B of the resin particle after compression release to the distance between the first surface 1a and the second surface 1b in the compression direction (the longest diameter B of the resin particle after compression release / the distance between the first surface 1a and the second surface 1b in the compression direction).
[0063] The particle size of the resin particles (before compression) can be appropriately set according to the application. The particle size of the resin particles (before compression) is preferably 0.5 μm or more, more preferably 1 μm or more, preferably 500 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. If the particle size of the resin particles is above the lower limit and below the upper limit, the resin particles can be further suitably used for conductive particles and spacers.
[0064] The particle size of the resin particles (before compression) is preferably an average particle size, preferably a number average particle size. As for the particle size of the resin particles, for example, it can be obtained by observing any 50 resin particles with an electron microscope or an optical microscope, calculating the average value of the particle size of each resin particle, or using a particle size distribution measuring device. In the observation using an electron microscope or an optical microscope, the particle size of each resin particle is obtained in the form of a particle size under a circular equivalent diameter. In the observation using an electron microscope or an optical microscope, the average particle size under a circular equivalent diameter of any 50 resin particles is almost equal to the average particle size under a spherical equivalent diameter. In terms of a particle size distribution measuring device, the particle size of each resin particle is obtained in the form of a particle size under a spherical equivalent diameter. The average particle size of the resin particles is preferably calculated using a particle size distribution measuring device.
[0065] In addition, when the particle size of the resin particles of the conductive particles is to be measured, for example, it can be measured as follows.
[0066] Conductive particles are added to "Technovit 4000" manufactured by Kulzer so that the content of the conductive particles is 30% by weight, and the conductive particles are dispersed to prepare an embedded resin body for conductive particle inspection. An ion milling device ("IM4000" manufactured by Hitachi High Technologies) is used to cut out the cross section of the conductive particles in the form of being dispersed near the center of the conductive particles in the embedded resin body for inspection. Then, using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 25,000 times, 50 conductive particles are randomly selected, and the resin particles of each conductive particle are observed. The particle size of the resin particles in each conductive particle is measured, and the arithmetic average is processed as the particle size of the resin particles.
[0067] The coefficient of variation (CV value) of the particle size of the resin particles is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less. When the CV value is below the upper limit, the resin particles can be more suitably used for conductive particles and spacers.
[0068] The CV value is represented by the following formula.
[0069] CV value (%) = (ρ / Dn) × 100
[0070] ρ: Standard deviation of the particle size of the resin particles
[0071] Dn: average particle size of resin particles
[0072] The shape of the resin particles (before compression) is not particularly limited. The shape of the resin particles (before compression) may be spherical, may be a shape other than a spherical shape, may be a flat shape, etc.
[0073] The thermal decomposition temperature of the resin particles is preferably 200° C. or higher, more preferably 220° C. or higher, and preferably 350° C. or lower, more preferably 300° C. or lower. When the thermal decomposition temperature of the resin particles is at least the lower limit and at most the upper limit, the shape of the resin particles after compression release can be improved, and the effect of the present invention can be more effectively exerted.
[0074] The thermal decomposition temperature can be measured using a differential thermogravimetric simultaneous measuring device (e.g., "TG / DTA: STA7200" manufactured by Hitachi Hig htech science). 10 mg of the resin particles are heated at a rate of 5°C / min in air, and the temperature at which the weight decreases by 10% is taken as the thermal decomposition temperature.
[0075] The compression modulus (10% K value) of the resin particles when compressed by 10% is preferably 100 N / mm 2 More than 500 N / mm 2 More than, more preferably 1000N / mm 2 Above, preferably 3500N / mm 2 Below, more preferably 3200N / mm 2 Below, more preferably 2800N / mm 2 When the 10% K value is not less than the above lower limit and not more than the above upper limit, the effects of the present invention can be more effectively exerted.
[0076] The compression modulus (30% K value) of the resin particles when compressed by 30% is preferably 100 N / mm 2 More than 300 N / mm 2 More preferably, 500 N / mm 2 Above, preferably 3000N / mm 2 Below, more preferably 2500N / mm 2 Below, more preferably 2000N / mm 2 When the 30% K value is not less than the above lower limit and not more than the above upper limit, the effects of the present invention can be more effectively exerted.
[0077] The compression modulus (10% K value and 30% K value) of the resin particles can be measured as follows.
[0078] Using a micro compression tester, a resin particle is compressed with the smooth indenter end face of a cylinder (diameter 50 μm, made of diamond) at 25°C, a compression speed of 0.3 mN / second, and a maximum test load of 20 mN. The load value (N) and the compression displacement (mm) at this time are measured. Based on the measured values obtained, the compression modulus (10% K value and 30% K value) can be calculated by the following formula. As the micro compression tester, for example, "Fisher scope H-100" manufactured by Fisher Company can be used. The compression modulus (10% K value and 30% K value) in the resin particle is preferably calculated by arithmetic averaging the compression modulus (10% K value and 30% K value) of 50 randomly selected resin particles.
[0079] 10% K value and 30% K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R -1 / 2
[0080] F: Load value when the resin particles are compressed by 10% or 30% (N)
[0081] S: Compression displacement when the resin particles are compressed by 10% or 30% (mm)
[0082] R: Radius of resin particles (mm)
[0083] The compression modulus generally and quantitatively indicates the hardness of the resin particles. By using the compression modulus, the hardness of the resin particles can be quantitatively and uniquely indicated.
[0084] The compression recovery rate of the resin particles is preferably 5% or more, more preferably 8% or more, and preferably 60% or less, more preferably 40% or less. When the compression recovery rate is above the lower limit and below the upper limit, the effect of the present invention can be more effectively exerted.
[0085] The compression recovery rate of the resin particles can be measured as follows.
[0086] Spread resin particles on the sample stage. For one of the scattered resin particles, use a micro compression tester, with a smooth indenter end face of a cylinder (diameter 50μm, made of diamond), at 25°C, in the center direction of the resin particle, apply a load (reverse load value) until the resin particle is compressed and deformed by 30%. Then, unload to the load value (0.40mN) at the origin. Measure the load-compression displacement between them, and the compression recovery rate can be obtained according to the following formula. It should be noted that the load speed is set to 0.33mN / second. As the micro compression tester, for example, "Fisher scope H-100" manufactured by Fisher Company can be used.
[0087] Compression recovery rate (%) = [L2 / L1] × 100
[0088] L1: Compression displacement from the origin load value to the reverse load value when the load is applied
[0089] L2: Unloading displacement from the reverse load value to the origin load value when the load is released
[0090] The use of the resin particles is not particularly limited. The resin particles can be suitably used for various uses. By changing the compression conditions of the resin particles during use, the thickness of the resin particles can be suitably changed.
[0091] The resin particles are preferably used as spacers, as adhesives for electronic components, for obtaining conductive particles having a conductive portion, or as materials for laminated molding. The resin particles are more preferably used as spacers, as adhesives for electronic components, or for obtaining conductive particles having a conductive portion. In the conductive particles, the conductive portion is formed on the surface of the resin particles.
[0092] The resin particles are preferably used as spacers or as spacers. As the method of using the spacer, spacers for liquid crystal display elements, spacers for interval control, spacers for stress relief, and spacers for dimming laminates can be cited. The spacer for interval control can be used in the interval control of laminated chips to ensure the height and flatness of the device, and in the interval control of optical parts to ensure the smoothness of the glass surface and the thickness of the adhesive layer. The spacer for stress relief can be used in stress relief of sensor chips, etc., and stress relief of the connecting portion connecting two connection object components. As the sensor chip, for example, a semiconductor sensor chip can be cited.
[0093] The resin particles are preferably used as spacers for liquid crystal display elements or as spacers for liquid crystal display elements, and are preferably used as peripheral sealants for liquid crystal display elements. In the peripheral sealant for liquid crystal display elements, the resin particles preferably function as spacers. The resin particles are preferably used as spacers for liquid crystal display, as adhesives for electronic components, or for obtaining conductive particles with conductive portions. Since the resin particles have good compression deformation characteristics, when the resin particles are used as spacers and arranged between substrates, or when conductive portions are formed on the surface and used as conductive particles to electrically connect electrodes, spacers or conductive particles can be efficiently arranged between substrates or between electrodes. In addition, as far as the resin particles are concerned, since the aggregation and movement of the spacers can be suppressed, poor connection and poor display are not easy to occur in the liquid crystal display element using the spacer for the liquid crystal display element and the connection structure using the conductive particles.
[0094] The resin particles are preferably used for adhesives for electronic parts or as adhesives for electronic parts. As the adhesive for electronic parts, adhesives for liquid crystal panels, adhesives for laminated substrates, adhesives for substrate circuits, and adhesives for camera modules can be cited. As the laminated substrate, for example, semiconductor sensor chips can be cited. The resin particles for adhesives for electronic parts or the resin particles used as adhesives for electronic parts are preferably adhesive resin particles with bonding performance. If the resin particles are adhesive resin particles, the resin particles and the laminated object parts can be well bonded when the crimped resin particles are cured. The resin particles can be used alone as adhesives for electronic parts. The resin particles can be used as adhesives for electronic parts without using other bonding components. When the resin particles are used for adhesives for electronic parts, they can be used alone as adhesives for electronic parts or together with other bonding components. In addition, when the resin particles are adhesive resin particles with bonding performance, they can be used as spacers and adhesives for electronic parts. When the resin particles are used as a spacer and adhesive for electronic components, physical properties required for the spacer, such as spacing controllability and stress relaxation, and adhesiveness can be more highly achieved than when the spacer and the adhesive are made of different materials.
[0095] The resin particles are preferably used for a laminated material. When the resin particles are used for the laminated material, for example, the resin particles can be three-dimensionally laminated to form a specific shape and then cured to form a three-dimensional object.
[0096] The following will describe other details of the resin particles. It should be noted that, in this specification, "(meth)acrylate" refers to one or both of "acrylate" and "methacrylate", and "(meth)acrylic acid" refers to one or both of "acrylic acid" and "methacrylic acid".
[0097] (Other details of resin particles)
[0098] The material of the resin particles is not particularly limited. The material of the resin particles is preferably an organic material. The resin particles may be particles having a porous structure or particles having a solid structure. The porous structure refers to a structure having a plurality of pores. The solid structure refers to a structure not having a plurality of pores.
[0099] In the case where various materials of resin particles are present as shown below, in the present invention, a material that satisfies the above-mentioned specific compression characteristics can be used.
[0100] As the organic material, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene can be cited; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenolic resin, melamine resin, benzoguanamine resin, urea formaldehyde resin, epoxy resin, polyurethane resin, isocyanate resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene ether, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, divinylbenzene polymer, and divinylbenzene copolymer, etc. As the divinylbenzene copolymer, etc., divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylate copolymer, etc. can be cited.
[0101] The material of the resin particles is preferably epoxy resin, melamine resin, benzoguanamine resin, polyurethane resin, isocyanate resin, polyimide resin, polyamide resin, polyamideimide resin, phenolic resin, or a polymer obtained by polymerizing one or more polymerizable monomers having ethylenically unsaturated groups. The material of the resin particles is more preferably epoxy resin, melamine resin, benzoguanamine resin, polyimide resin, polyamide resin, polyamideimide resin, phenolic resin, or a polymer obtained by polymerizing one or more polymerizable monomers having ethylenically unsaturated groups. The material of the resin particles further preferably includes a thermosetting resin. As the thermosetting resin, for example, epoxy resin, melamine resin, polyurethane resin, polyimide resin, and phenolic resin can be cited, but other thermosetting resins can also be used. The material of the resin particles is particularly preferably epoxy resin. If the material of the resin particles satisfies the preferred embodiment, the compression characteristics of the resin particles can be further easily controlled within the preferred range.
[0102] When an epoxy resin is used as the material of the resin particles, the epoxy resin is preferably a multifunctional epoxy resin. Examples of the epoxy resin include bifunctional epoxy resins such as bisphenol A epoxy resin and bisphenol F epoxy resin, trifunctional epoxy resins such as triazine epoxy resin and glycidylamine epoxy resin, and tetrafunctional epoxy resins such as tetraphenolethane epoxy resin and glycidylamine epoxy resin. The epoxy resin may be used alone or in combination of two or more.
[0103] In addition, when epoxy resin is used as the material of the resin particles, it is preferred to use a curing agent together with the epoxy resin. The curing agent thermally cures the epoxy resin. The curing agent is not particularly limited. As the curing agent, thiol curing agents such as imidazole curing agents, amine curing agents, phenol curing agents, and polythiol curing agents, as well as acid anhydride curing agents, can be cited. The thermal curing agent can be used alone or in combination of two or more. From the viewpoint of being easy to control the compression characteristics of the resin particles within a suitable range, the curing agent is preferably an amine curing agent.
[0104] The imidazole curing agent is not particularly limited. Examples of the imidazole curing agent include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid addition product, 2-phenyl-4,5-dihydroxymethylimidazole, Imidazole compounds in which the hydrogen at the 5-position of 1H-imidazole in 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4-benzyl-5-hydroxymethylimidazole, 2-p-tolyl-4-methyl-5-hydroxymethylimidazole, 2-m-tolyl-4,5-dihydroxymethylimidazole, 2-p-tolyl-4,5-dihydroxymethylimidazole, etc. is substituted with a hydroxymethyl group, and the hydrogen at the 2-position is substituted with a phenyl group or a tolyl group.
[0105] The thiol curing agent is not particularly limited, and examples of the thiol curing agent include trimethylolpropane tris-3-mercaptopropionate, pentaerythritol tetrakis-3-mercaptopropionate, and dipentaerythritol hexa-3-mercaptopropionate.
[0106] The amine curing agent is not particularly limited. As the amine curing agent, ethylenediamine, hexamethylenediamine, octamethylenediamine, decamethylenediamine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraspiro[5.5]undecane, bis(4-aminocyclohexyl)methane, norbornanediamine, phenylenediamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, metaphenylenediamine, diaminodiphenylmethane, diaminophenyl ether, metaxylene diamine, diaminonaphthalene, bisaminomethylcyclohexane, and diaminodiphenyl sulfone can be cited. From the viewpoint of easily controlling the compression characteristics of the resin particles within a suitable range, the amine curing agent is preferably ethylenediamine, hexamethylenediamine, octamethylenediamine, metaphenylenediamine, diaminodiphenyl sulfone, phenylenediamine, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane. From the viewpoint of easily controlling the compression characteristics of the resin particles within a suitable range, the amine curing agent is more preferably ethylenediamine, norbornanediamine, diaminodiphenylmethane, phenylenediamine, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane.
[0107] The acid anhydride curing agent is not particularly limited, and can be widely used as long as it is an acid anhydride used as a curing agent for thermosetting compounds such as epoxy compounds. As the acid anhydride curing agent, phthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, anhydride of phthalic anhydride derivatives, maleic anhydride, nadic anhydride, methylnadic anhydride, glutaric anhydride, succinic anhydride, glycerol dianhydrous trimellitic acid monoacetate, and ethylene glycol ditrimellitate Anhydride and other bifunctional acid anhydride curing agents, trifunctional acid anhydride curing agents such as trimellitic anhydride, and pyromellitic anhydride, benzophenone tetracarboxylic anhydride, methylcyclohexene tetracarboxylic anhydride, and polyazelene anhydride and other acid anhydride curing agents with more than four functions.
[0108] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, examples of the polymerizable monomer having an ethylenically unsaturated group include non-crosslinking monomers and crosslinking monomers.
[0109] As for the non-crosslinking monomers, as the vinyl compound, there can be mentioned styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; as (meth)acrylic acid compounds, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate Alkyl (meth)acrylate compounds such as ester, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylate compounds containing oxygen atoms such as 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; as α-olefin compounds, olefin compounds such as diisobutylene, isobutylene, linear olefins, ethylene, and propylene can be mentioned; as conjugated diene compounds, isoprene, butadiene, etc. can be mentioned.
[0110] As for the crosslinking monomer, as a vinyl compound, there can be mentioned vinyl monomers such as divinylbenzene, 1,4-dienyloxybutane, and divinyl sulfone; as a (meth)acrylic compound, there can be mentioned tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol Examples of the present invention include polyfunctional (meth)acrylate compounds such as di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate; examples of allyl compounds include triallyl (iso)cyanurate, triallyl trimellitate, diallyl phthalate, diallyl acrylamide, and diallyl ether; examples of silane compounds include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexane Alkoxysilane compounds such as phenyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, diphenyldimethoxysilane; vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methyl Alkoxysilanes containing polymerizable double bonds such as 1-vinyldimethoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-phenylvinyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as single-end modified silicone oils, double-end silicone oils, and side chain silicone oils; monomers containing carboxyl groups such as (meth)acrylic acid, maleic acid, and maleic anhydride; and the like.
[0111] The resin particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group. The polymerization method is not particularly limited, and examples thereof include free radical polymerization, ionic polymerization, polycondensation (condensation polymerization, polycondensation), addition condensation, living polymerization, and known methods such as living free radical polymerization. In addition, as other polymerization methods, suspension polymerization in the presence of a free radical polymerization initiator can be cited.
[0112] (Conductive particles)
[0113] The said electroconductive particle has the said resin particle and the electroconductive part arrange|positioned on the surface of the said resin particle.
[0114] Figure 2 It is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.
[0115] Figure 2 The conductive particle 11 shown has a resin particle 1 and a conductive portion 2 disposed on the surface of the resin particle 1. The conductive portion 2 covers the surface of the resin particle 1. The conductive particle 11 is a coated particle in which the surface of the resin particle 1 is coated with the conductive portion 2.
[0116] Figure 3 It is a cross-sectional view showing the conductive particles according to the second embodiment of the present invention.
[0117] Figure 3 The conductive particle 21 shown has a resin particle 1 and a conductive portion 22 disposed on the surface of the resin particle 1. Figure 3 In the conductive particles 21 shown, only the conductive portion 22 is Figure 2 The conductive particles 11 shown are different. The conductive portion 22 has a first conductive portion 22A as an inner layer and a second conductive portion 22B as an outer layer. The first conductive portion 22A is arranged on the surface of the resin particle 1. The second conductive portion 22B is arranged on the surface of the first conductive portion 22A.
[0118] Figure 4 It is a cross-sectional view showing the conductive particles according to the third embodiment of the present invention.
[0119] Figure 4 The conductive particle 31 shown includes a resin particle 1 , a conductive portion 32 , a plurality of core substances 33 , and a plurality of insulating substances 34 .
[0120] The conductive part 32 is arranged on the surface of the resin particle 1. The conductive particle 31 has a plurality of protrusions 31a on the conductive surface. The conductive part 32 has a plurality of protrusions 32a on the outer surface. In this way, the conductive particle may have protrusions on the conductive surface of the conductive particle or on the outer surface of the conductive part. A plurality of core materials 33 are arranged on the surface of the resin particle 1. A plurality of core materials 33 are embedded in the conductive part 32. The core material 33 is arranged on the inner side of the protrusions 31a and 32a. The conductive part 32 covers the plurality of core materials 33. Due to the plurality of core materials 33, the outer surface of the conductive part 32 is raised to form the protrusions 31a and 32a.
[0121] The conductive particles 31 have an insulating substance 34 disposed on the outer surface of the conductive portion 32. At least a portion of the outer surface of the conductive portion 32 is covered with the insulating substance 34. The insulating substance 34 is formed of a material having insulating properties and is an insulating particle. In this way, the conductive particles may have an insulating substance disposed on the outer surface of the conductive portion.
[0122] The metal used to form the conductive portion is not particularly limited. As the metal, gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum and their alloys can be cited. In addition, as the metal, tin-doped indium oxide (ITO) and solder can be cited. From the viewpoint of further improving the connection reliability between electrodes, the metal is preferably an alloy containing tin, nickel, palladium, copper or gold, preferably nickel or palladium.
[0123] As in the conductive particles 11 and 31, the conductive portion may be formed by one layer. As in the conductive particle 21, the conductive portion may also be formed by a plurality of layers. That is, the conductive portion may have a laminated structure of more than two layers. In the case where the conductive portion is formed by a plurality of layers, the outermost layer is preferably a gold layer, a nickel layer, a palladium layer, a copper layer or an alloy layer containing tin and silver, and more preferably a gold layer. If the outermost layer is these preferred conductive portions, the connection reliability between the electrodes can be further improved. In addition, if the outermost layer is a gold layer, the corrosion resistance can be further improved.
[0124] The method for forming the conductive portion on the surface of the resin particles is not particularly limited. As the method for forming the conductive portion, a method based on electroless plating, a method based on electroplating, a method based on physical vapor deposition, and a method of coating a metal powder or a paste containing a metal powder and an adhesive on the surface of the resin particles can be cited. From the viewpoint of further facilitating the formation of the conductive portion, a method based on electroless plating is preferred. As the method based on physical vapor deposition, methods such as vacuum evaporation, ion plating, and ion sputtering can be cited.
[0125] The compression modulus (10% K value) of the conductive particles when compressed by 10% is preferably 1000 N / mm 2 More preferably 3000N / mm 2 More than 4500 N / mm 2 Above, preferably 10000N / mm 2 Below, more preferably 9000N / mm 2 Below, more preferably 8000N / mm 2 When the 10% K value is not less than the above lower limit and not more than the above upper limit, the effects of the present invention can be more effectively exerted.
[0126] The compression modulus (30% K value) of the conductive particles when compressed by 30% is preferably 1000 N / mm 2 More preferably 3000N / mm 2 More than 4500 N / mm 2 Above, preferably 10000N / mm 2 Below, more preferably 8000N / mm 2 Below, more preferably 6000N / mm 2 When the 30% K value is not less than the above lower limit and not more than the above upper limit, the effects of the present invention can be more effectively exerted.
[0127] The compression modulus (10% K value and 30% K value) in the conductive particles can be measured by the same method as the compression modulus (10% K value and 30% K value) in the resin particles.
[0128] The compression modulus generally and quantitatively indicates the hardness of the conductive particles. By using the compression modulus, the hardness of the conductive particles can be quantitatively and uniquely indicated.
[0129] The compression recovery rate of the conductive particles is preferably 5% or more, more preferably 8% or more, and preferably 60% or less, more preferably 40% or less. When the compression recovery rate is at least the lower limit and at most the upper limit, the effect of the present invention can be more effectively exerted.
[0130] The compression recovery rate of the conductive particles can be measured in the same manner as the compression recovery rate of the resin particles.
[0131] The particle size of the conductive particles is preferably 0.5 μm or more, more preferably 1.0 μm or more, preferably 500 μm or less, more preferably 450 μm or less, further preferably 100 μm or less, further preferably 50 μm or less, and particularly preferably 20 μm or less. If the particle size of the conductive particles is above the lower limit and below the upper limit, when the conductive particles are used to connect the electrodes, the contact area between the conductive particles and the electrodes becomes sufficiently large, and it is not easy to form condensed conductive particles when forming the conductive part. In addition, the interval between the electrodes connected by the conductive particles will not become too large, and the conductive part becomes difficult to peel off from the surface of the resin particles. In addition, if the particle size of the conductive particles is above the lower limit and below the upper limit, the conductive particles can be suitably used for the purpose of conductive materials.
[0132] The particle diameter of the conductive particles is a diameter when the conductive particles are in a true spherical shape. If the conductive particles are in a shape other than a true spherical shape, the particle diameter is a diameter when a true sphere having a volume equivalent to the conductive particles is assumed.
[0133] The particle size of the conductive particles is preferably an average particle size, more preferably a number average particle size. The particle size of the conductive particles can be obtained by observing any 50 conductive particles with an electron microscope or an optical microscope, calculating the average value, or performing a laser diffraction particle size distribution measurement. In the observation performed by an electron microscope or an optical microscope, the particle size of each conductive particle is obtained in the form of a particle size under a circular equivalent diameter. In the observation performed by an electron microscope or an optical microscope, the average particle size under a circular equivalent diameter of any 50 conductive particles is almost equal to the average particle size under a spherical equivalent diameter. In the laser diffraction particle size distribution measurement, the particle size of each conductive particle is obtained in the form of a particle size under a spherical equivalent diameter. The particle size of the conductive particles is preferably calculated by laser diffraction particle size distribution measurement.
[0134] The thickness of the conductive portion is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 10 μm or less, more preferably 1 μm or less, and further preferably 0.3 μm or less. In the case where the conductive portion is multilayer, the thickness of the conductive portion is the thickness of the conductive portion as a whole. If the thickness of the conductive portion is above the lower limit and below the upper limit, sufficient conductivity can be obtained, and the conductive particles will not become too hard, and the conductive particles will be fully deformed when connected between electrodes.
[0135] In the case where the conductive portion is formed by a plurality of layers, the thickness of the conductive portion of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, preferably 0.5 μm or less, and more preferably 0.1 μm or less. If the thickness of the conductive portion of the outermost layer is above the lower limit and below the upper limit, the coating based on the conductive portion of the outermost layer becomes uniform, the corrosion resistance is sufficiently improved, and the connection reliability between the electrodes can be further improved. In addition, in the case where the outermost layer is a gold layer, the thinner the thickness of the gold layer, the lower the cost.
[0136] The thickness of the conductive part can be measured, for example, by observing the cross section of the conductive particle using a transmission electron microscope (TEM). Regarding the thickness of the conductive part, it is preferred to calculate the average value of the thickness of the conductive part at any 5 locations as the thickness of the conductive part of one conductive particle, and it is more preferred to calculate the average value of the thickness of the conductive part as a whole as the thickness of the conductive part of one conductive particle. As for the thickness of the conductive part, it is preferred to calculate the average value of the thickness of the conductive part of each conductive particle for any 50 conductive particles.
[0137] The conductive particles preferably have protrusions on the outer surface of the conductive portion. The conductive particles preferably have protrusions on the conductive surface. The protrusions are preferably multiple. An oxide film is often formed on the surface of the conductive portion and the surface of the electrode connected by the conductive particles. In the case of using conductive particles with protrusions, by arranging the conductive particles between the electrodes and crimping them, the oxide film is effectively excluded due to the protrusions. Therefore, the electrode and the conductive portion of the conductive particles can be further reliably contacted, and the connection resistance between the electrodes can be further reduced. In addition, in the case where the conductive particles have an insulating substance on the surface, or in the case where the conductive particles are dispersed in a binder resin and used as a conductive material, the insulating substance or binder resin between the conductive particles and the electrodes can be further effectively excluded by the protrusions of the conductive particles. Therefore, the connection reliability between the electrodes can be further improved.
[0138] As a method for forming a protrusion on the surface of the conductive particle, there can be cited a method of attaching a core material to the surface of a resin particle and then forming a conductive portion by electroless plating; and a method of attaching a core material after forming a conductive portion by electroless plating on the surface of a resin particle, and further forming a conductive portion by electroless plating, etc. In addition, in order to form the protrusion, the core material may not be used.
[0139] As a method for forming the protrusion, the following methods can also be cited. A method of adding a core material in the middle stage of forming a conductive portion by electroless plating on the surface of a resin particle. As a method of forming a protrusion by electroless plating without using a core material, a method of generating a metal core by electroless plating, attaching the metal core to the surface of a resin particle or a conductive portion, and further forming a conductive portion by electroless plating.
[0140] The conductive particles preferably further include an insulating substance disposed on the outer surface of the conductive portion. In this case, when the conductive particles are used for connection between electrodes, short circuits between adjacent electrodes can be prevented. Specifically, when a plurality of conductive particles are in contact, since there is an insulating substance between the plurality of electrodes, short circuits between laterally adjacent electrodes rather than between upper and lower electrodes can be prevented. It should be noted that, when connecting between electrodes, by pressurizing the conductive particles with two electrodes, the insulating substance between the conductive portion of the conductive particles and the electrode can be easily removed. In the case where the conductive particles have protrusions on the surface of the conductive portion, the insulating substance between the conductive portion of the conductive particles and the electrode can be further easily removed. The insulating substance is preferably an insulating resin layer or insulating particles, more preferably insulating particles. The insulating particles are preferably insulating resin particles.
[0141] The outer surface of the conductive part and the surface of the insulating particles may be coated with a compound having a reactive functional group. The outer surface of the conductive part and the surface of the insulating particles may not be directly chemically bonded, but may be indirectly chemically bonded through a compound having a reactive functional group. After a carboxyl group is introduced on the outer surface of the conductive part, the carboxyl group may be chemically bonded to a functional group on the surface of the insulating particles via a polymer electrolyte such as polyethyleneimine.
[0142] (Conductive materials)
[0143] The conductive material comprises the conductive particles and a binder resin. The conductive particles are preferably dispersed in a binder resin and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material can be used for electrical connection of electrodes. The conductive material is preferably a circuit connection material.
[0144] There is no particular limitation on the binder resin. As the binder resin, a known insulating resin can be used. The binder resin preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. As the curable component, for example, a photocurable component and a thermosetting component can be listed. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent. As the binder resin, for example, vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers and elastomers can be listed. The binder resin can be used alone or in combination of two or more.
[0145] As the vinyl resin, for example, vinyl acetate resin, acrylic resin and styrene resin can be listed. As the thermoplastic resin, for example, polyolefin resin, ethylene-vinyl acetate copolymer and polyamide resin can be listed. As the curable resin, for example, epoxy resin, polyurethane resin, polyimide resin and unsaturated polyester resin can be listed. It should be noted that the curable resin can also be a room temperature curing resin, a thermosetting resin, a light curing resin or a moisture curing resin. The curable resin can be used in combination with a curing agent. As the thermoplastic block copolymer, for example, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer hydrogenated product and styrene-isoprene-styrene block copolymer hydrogenated product can be listed. As the elastomer, for example, styrene-butadiene copolymer rubber and acrylonitrile-styrene block copolymer rubber can be listed.
[0146] In addition to the conductive particles and the adhesive resin, the conductive material may also contain various additives such as fillers, extenders, softeners, plasticizers, polymerization catalysts, curing catalysts, colorants, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents and flame retardants.
[0147] As a method for dispersing the conductive particles in the adhesive resin, a conventionally known dispersion method can be used without particular limitation. As a method for dispersing the conductive particles in the adhesive resin, for example, the following methods can be cited. A method in which the conductive particles are added to the adhesive resin, and then kneaded and dispersed using a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, and then added to the adhesive resin, and then kneaded and dispersed using a planetary mixer or the like. A method in which the conductive particles are diluted with water or an organic solvent, and then added to the adhesive resin, and then kneaded and dispersed using a planetary mixer or the like.
[0148] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, preferably 400 Pa·s or less, and more preferably 300 Pa·s or less. If the viscosity of the conductive material at 25°C is above the lower limit and below the upper limit, the connection reliability between the electrodes can be further effectively improved. The viscosity (η25) can be appropriately adjusted according to the type and amount of the compounding component.
[0149] The viscosity (η25) can be measured under the conditions of 25° C. and 5 rpm using, for example, an E-type viscometer (“TVE22L” manufactured by Toki Sangyo Co., Ltd.).
[0150] The conductive material can also be used as a conductive paste and a conductive film. If the conductive material of the present invention is a conductive film, a film without conductive particles can be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.
[0151] In 100 wt % of the conductive material, the content of the binder resin is preferably 10 wt % or more, more preferably 30 wt % or more, further preferably 50 wt % or more, particularly preferably 70 wt % or more, preferably 99.99 wt % or less, more preferably 99.9 wt % or less. If the content of the binder resin is above the lower limit and below the upper limit, the conductive particles are efficiently arranged between the electrodes, and the connection reliability of the connection object parts connected by the conductive material is further improved.
[0152] In 100 wt % of the conductive material, the content of the conductive particles is preferably 0.01 wt % or more, more preferably 0.1 wt % or more, preferably 80 wt % or less, more preferably 60 wt % or less, further preferably 40 wt % or less, further preferably 20 wt % or less, and particularly preferably 10 wt % or less. If the content of the conductive particles is above the lower limit and below the upper limit, the connection resistance between the electrodes can be further effectively reduced, and the connection reliability between the electrodes can be further effectively improved.
[0153] (Connection structure)
[0154] By connecting connection target members using the resin particles, a connection structure can be obtained.
[0155] The connection structure using the resin particles comprises: a first connection object part, a second connection object part, and a connection portion connecting the first connection object part and the second connection object part. In the connection structure, the connection portion is formed by the resin particles or a composition containing the resin particles. In the connection structure using the resin particles, it is preferred that the resin particles are directly in contact with the first connection object part and the second connection object part.
[0156] A connection structure can be obtained by connecting connection target members using the conductive particles or a conductive material containing the conductive particles and a binder resin.
[0157] The connection structure using the conductive particles comprises: a first connection object part having a first electrode on its surface, a second connection object part having a second electrode on its surface, and a connection portion connecting the first connection object part and the second connection object part. In the connection structure, the connection portion is formed by conductive particles, or is formed by a conductive material containing the conductive particles and a binder resin. The conductive particles comprise the resin particles and a conductive portion arranged on the surface of the resin particles. In the connection structure, the first electrode and the second electrode are electrically connected via the conductive particles.
[0158] When the conductive particles are used alone, the connection portion itself is the conductive particles. That is, the first connection object member and the second connection object member are connected via the conductive particles. The conductive material for obtaining the connection structure is preferably an anisotropic conductive material.
[0159] Figure 5 This is a cross-sectional view showing an example of a connection structure using the conductive particles according to the first embodiment of the present invention.
[0160] Figure 5 The connection structure 41 shown includes a first connection object member 42, a second connection object member 43, and a connection portion 44 connecting the first connection object member 42 and the second connection object member 43. The connection portion 44 is formed of a conductive material containing conductive particles 11 and a binder resin. Figure 5 In the figure, for the convenience of illustration, the conductive particles 11 are schematically shown. Instead of the conductive particles 11, other conductive particles such as the conductive particles 21 and 31 may be used.
[0161] The first connection object member 42 has a plurality of first electrodes 42a on the surface (upper surface). The second connection object member 43 has a plurality of second electrodes 43a on the surface (lower surface). The first electrode 42a and the second electrode 43a are electrically connected via one or more conductive particles 11. Therefore, the first and second connection object members 42 and 43 are electrically connected via the conductive particles 11.
[0162] The method for manufacturing the connection structure is not particularly limited. As an example of the method for manufacturing the connection structure, there can be cited a method in which the conductive material is arranged between the first connection object component and the second connection object component, and after obtaining a laminate, the laminate is heated and pressurized. The pressure during the pressurization is preferably 40 MPa or more, more preferably 60 MPa or more, preferably 90 MPa or less, and more preferably 70 MPa or less. The temperature during the heating is preferably 80°C or more, more preferably 100°C or more, preferably 140°C or less, and more preferably 120°C or less.
[0163] The first connection object component and the second connection object component are not particularly limited. Specifically, the first connection object component and the second connection object component include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, and electronic components such as circuit substrates such as resin films, printed substrates, flexible printed substrates, flexible flat cables, rigid-flexible boards, glass epoxy substrates, and glass substrates. The first connection object component and the second connection object component are preferably electronic components.
[0164] The conductive material is preferably a conductive material for connecting electronic components. The conductive paste is a paste-like conductive material, and is preferably applied to the connection target component in a paste-like state.
[0165] The conductive particles, the conductive material and the connecting material may also be applied to a touch panel. Therefore, the connection object component is preferably a flexible substrate, or a connection object component having an electrode disposed on the surface of a resin film. The connection object component is preferably a flexible substrate, preferably a connection object component having an electrode disposed on the surface of a resin film. When the flexible substrate is a flexible printed substrate, etc., the flexible substrate generally has an electrode on the surface.
[0166] As the electrode provided on the connection object part, metal electrodes such as gold electrode, nickel electrode, tin electrode, aluminum electrode, copper electrode, molybdenum electrode, silver electrode, SUS electrode, and tungsten electrode can be cited. When the connection object part is a flexible printed circuit board, the electrode is preferably a gold electrode, a nickel electrode, a tin electrode, a silver electrode or a copper electrode. When the connection object part is a glass substrate, the electrode is preferably an aluminum electrode, a copper electrode, a molybdenum electrode or a tungsten electrode. It should be noted that when the electrode is an aluminum electrode, it can be an electrode formed by aluminum alone, or it can be an electrode with an aluminum layer stacked on the surface of a metal oxide layer. As the material of the metal oxide layer, indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element can be cited. As the trivalent metal element, Sn, Al, Ga, etc. can be cited.
[0167] In addition, the resin particles can be suitably used as spacers for liquid crystal display elements. The first connection object component can be a first liquid crystal display element component. The second connection object component can be a second liquid crystal display element component. The connecting portion can be a sealing portion that seals the periphery of the first liquid crystal display element component and the second liquid crystal display element component in a state where the first liquid crystal display element component and the second liquid crystal display element component are relative to each other.
[0168] The resin particles can be used in a peripheral sealant for a liquid crystal display element. The liquid crystal display element comprises a first liquid crystal display element component and a second liquid crystal display element component. The liquid crystal display element further comprises: a sealing portion for sealing the periphery of the first liquid crystal display element component and the second liquid crystal display element component in a state where the first liquid crystal display element component and the second liquid crystal display element component are opposite to each other; and a liquid crystal is arranged between the first liquid crystal display element component and the second liquid crystal display element component on the inner side of the sealing portion. For this liquid crystal display element, a liquid crystal dropping method is applied, and the sealing portion is formed by thermally curing a sealant for the liquid crystal dropping method.
[0169] The liquid crystal display element has a thickness of 1 mm 2 The arrangement density of the spacers for liquid crystal display elements is preferably 10 / mm 2 More than, preferably 1000 pieces / mm 2 Below. If the configuration density is 10 pieces / mm 2 If the above arrangement density is 1000 cells / mm 2 Below, the contrast of the liquid crystal display element becomes better.
[0170] (Electronic components device)
[0171] The resin particles or conductive particles may be disposed between the first ceramic member and the second ceramic member in the outer periphery of the first ceramic member and the second ceramic member, and used as a gap control material and a conductive connecting material.
[0172] Figure 6 This is a cross-sectional view showing an example of an electronic component device using the resin particles according to the present invention. Figure 7 For the general Figure 6 The figure is a cross-sectional view showing an enlarged view of a joint portion in the electronic component device shown.
[0173] Figure 6 , 7 The electronic component device 81 shown includes a first ceramic member 82 , a second ceramic member 83 , a bonding portion 84 , an electronic component 85 , and a lead frame 86 .
[0174] The first and second ceramic components 82 and 83 are respectively formed of ceramic materials. The first and second ceramic components 82 and 83 are respectively, for example, housings. The first ceramic component 82 is, for example, a substrate. The second ceramic component 83 is, for example, a cover. The first ceramic component 82 has a convex portion protruding toward the second ceramic component 83 side (upper side) on the outer periphery. The first ceramic component 82 has a concave portion forming an internal space R for accommodating the electronic component 85 on the second ceramic component 83 side (upper side). It should be noted that the first ceramic component 82 may not have a convex portion. The second ceramic component 83 has a convex portion protruding toward the first ceramic component 82 side (lower side) on the outer periphery. The second ceramic component 83 has a concave portion forming an internal space R for accommodating the electronic component 85 on the first ceramic component 82 side (lower side). It should be noted that the second ceramic component 83 may not have a convex portion. The internal space R is formed by the first ceramic component 82 and the second ceramic component 83.
[0175] The joining portion 84 joins the outer peripheral portion of the first ceramic member 82 and the outer peripheral portion of the second ceramic member 83. Specifically, the joining portion 84 joins the convex portion of the outer peripheral portion of the first ceramic member 82 and the convex portion of the outer peripheral portion of the second ceramic member 83.
[0176] A package is formed by the first and second ceramic members 82 and 83 joined by the joining portion 84. The package forms an internal space R. The joining portion 84 seals the internal space R in a liquid-tight and air-tight manner. The joining portion 84 is a sealing portion.
[0177] The electronic component 85 is disposed in the internal space R of the package. Specifically, the electronic component 85 is disposed on the first ceramic member 82. In the present embodiment, two electronic components 85 are used.
[0178] The bonding part 84 includes a plurality of resin particles 1 and glass 84B. The bonding part 84 is formed using a bonding material including a plurality of resin particles 1 different from glass particles and glass 84B. The bonding material is a bonding material for ceramic packaging. The bonding material may include the conductive particles instead of the resin particles.
[0179] The bonding material may contain a solvent or a resin. In the bonding portion 84 , glass 84B such as glass particles is melted and bonded and then solidified.
[0180] Examples of electronic components include sensor elements, MEMS, and bare chips. Examples of the sensor elements include pressure sensor elements, acceleration sensor elements, CMOS sensor elements, CCD sensor elements, and housings of the various sensor elements.
[0181] The lead frame 86 is disposed between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83. The lead frame 86 extends toward the inner space R and the outer space of the package. The terminal of the electronic component 85 and the lead frame 86 are electrically connected via a wire.
[0182] The joint portion 84 directly joins a portion of the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83, and joins a portion thereof indirectly. Specifically, the joint portion 84 indirectly joins the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83 via the lead frame 86 in a portion between the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83 where the lead frame 86 exists. In a portion between the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83 where the lead frame 86 exists, the first ceramic component 82 is in contact with the lead frame 86, and the lead frame 86 is in contact with the first ceramic component 82 and the joint portion 84. Furthermore, the joint portion 84 is in contact with the lead frame 86 and the second ceramic component 83, and the second ceramic component 83 is in contact with the joint portion 84. The bonding portion 84 directly bonds the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83 in a portion where the lead frame 86 does not exist between the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83. The bonding portion 84 is in contact with the first ceramic component 82 and the second ceramic component 83 in a portion where the lead frame 86 does not exist between the outer periphery of the first ceramic component 82 and the outer periphery of the second ceramic component 83.
[0183] In the portion where lead frame 86 is present between the periphery of first ceramic member 82 and the periphery of second ceramic member 83 , the distance of the gap between the periphery of first ceramic member 82 and the periphery of second ceramic member 83 is controlled by the plurality of resin particles 1 included in bonding portion 84 .
[0184] The bonding portion may directly or indirectly bond the outer peripheral portion of the first ceramic member and the outer peripheral portion of the second ceramic member. It should be noted that an electrical connection method other than a lead frame may be used.
[0185] For example, the electronic component device 81 may include: a first ceramic component formed of a ceramic material, a second ceramic component formed of a ceramic material, a joint, and an electronic component. In the electronic component device, the joint may directly or indirectly join the outer periphery of the first ceramic component and the outer periphery of the second ceramic component. In the electronic component device, a package may be formed by the first and second ceramic components joined by the joint. In the electronic component device, the electronic component is arranged in an internal space of the package, and the joint may include a plurality of resin particles and glass.
[0186] In addition, as the bonding material used in the electronic component device 81, the bonding material for ceramic packaging is used in the electronic component device to form the bonding portion and contains resin particles and glass. It should be noted that an electrical connection method that only contains resin particles and does not contain glass can also be used. In addition, the bonding portion can contain the conductive particles instead of the resin particles.
[0187] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0188] (Example 1)
[0189] (1) Preparation of resin particles
[0190] In a reaction container equipped with a thermometer, a stirrer, and a condenser, 15 parts by weight of bisphenol A epoxy resin ("EXA-850-CRP" manufactured by DIC Corporation), 7.5 parts by weight of polyvinyl pyrrolidone as a dispersion stabilizer, and 250 parts by weight of ethanol were added, and the mixture was uniformly dissolved by stirring at 68°C for 1 hour. Next, 4.25 parts by weight of 4,4'-diaminodiphenylmethane and 35 parts by weight of ethanol were added, uniformly dissolved, and then added to the reaction container, and reacted at 68°C for 20 hours to obtain a reaction product. The obtained reaction product was washed and dried to obtain resin particles.
[0191] (2) Preparation of conductive particles
[0192] 10 parts by weight of the obtained resin particles were dispersed in 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, and then the resin particles were taken out by filtering the solution. Next, the resin particles were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the resin particles. After the surface-activated resin particles were fully washed with water, they were added to 500 parts by weight of distilled water and dispersed, thereby obtaining a dispersion.
[0193] Separately, a nickel plating solution (pH 8.5) containing 0.35 mol / L nickel sulfate, 1.38 mol / L dimethylamine borane, and 0.5 mol / L sodium citrate was prepared.
[0194] The nickel plating solution was slowly added dropwise to the obtained dispersion while stirring at 60° C. to perform electroless nickel plating. Subsequently, the dispersion was filtered to remove particles, which were washed with water and dried to form a nickel-boron conductive layer on the surface of the resin particles, thereby obtaining conductive particles having a conductive portion on the surface.
[0195] (3) Production of conductive material (anisotropic conductive paste)
[0196] 7 parts by weight of the obtained conductive particles, 25 parts by weight of bisphenol A type phenoxy resin, 4 parts by weight of fluorene type epoxy resin, 30 parts by weight of phenol novolac type epoxy resin, and SI-60L (manufactured by Sanshin Chemical Industry Co., Ltd.) were mixed, defoamed and stirred for 3 minutes, thereby obtaining a conductive material (anisotropic conductive paste).
[0197] (4) Fabrication of the connection structure
[0198] A transparent glass substrate (first connection object component) having an IZO electrode pattern (first electrode, the Vickers hardness of the metal on the electrode surface is 100Hv) with an L / S of 10μm / 10μm formed on the upper surface is prepared. In addition, a semiconductor chip (second connection object component) having an Au electrode pattern (second electrode, the Vickers hardness of the metal on the electrode surface is 50Hv) with an L / S of 10μm / 10μm formed on the lower surface is prepared. The obtained anisotropic conductive paste is coated on the transparent glass substrate to a thickness of 30μm to form an anisotropic conductive paste layer. Subsequently, the semiconductor chip is stacked on the anisotropic conductive paste layer in a manner such that the electrodes are opposite to each other. Thereafter, while adjusting the temperature of the pressurized heating head so that the anisotropic conductive paste layer is 100°C, the pressurized heating head is placed on the upper surface of the semiconductor chip, and a pressure of 55MPa is applied to cure the anisotropic conductive paste layer at 100°C, thereby obtaining a connection structure.
[0199] (Example 2)
[0200] When preparing the resin particles, glycidylamine epoxy resin ("TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.) was used instead of bisphenol A epoxy resin, and isopropyl alcohol was used instead of ethanol. In addition, the amount of 4,4'-diaminodiphenylmethane added when preparing the resin particles was changed to 7.53 parts by weight. Except for the above changes, resin particles, conductive particles, conductive materials, and connected structures were obtained in the same manner as in Example 1.
[0201] (Example 3)
[0202] When preparing the resin particles, a triazine epoxy resin ("TEPIC-PAS" manufactured by Nissan Chemical Co., Ltd.) was used instead of a bisphenol A epoxy resin. In addition, when preparing the resin particles, 1.63 parts by weight of ethylenediamine was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. Except for the above changes, the resin particles, conductive particles, conductive materials, and connected structures were obtained in the same manner as in Example 1.
[0203] (Example 4)
[0204] When preparing the resin particles, a glycidylamine epoxy resin ("JER-630" manufactured by Mitsubishi Chemical Corporation) was used instead of the bisphenol A epoxy resin. In addition, the amount of 4,4'-diaminodiphenylmethane added when preparing the resin particles was changed to 7.63 parts by weight. Except for the above changes, the resin particles, conductive particles, conductive materials, and connected structures were obtained in the same manner as in Example 1.
[0205] (Example 5)
[0206] When preparing resin particles, alicyclic glycidylamine epoxy resin ("TETRAD-C" manufactured by Mitsubishi Gas Chemical Co., Ltd.) was used instead of bisphenol A epoxy resin, and isopropyl alcohol was used instead of ethanol. In addition, the amount of 4,4'-diaminodiphenylmethane added when preparing resin particles was changed to 7.44 parts by weight. Except for the above changes, resin particles, conductive particles, conductive materials, and connected structures were obtained in the same manner as in Example 1.
[0207] (Example 6)
[0208] Resin particles were obtained in the same manner as in Example 1. When preparing the conductive particles, 1 g of nickel particle slurry (average particle size 100 nm) was added to the dispersion over 3 minutes to obtain a suspension containing resin particles with core material attached. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1 except that the suspension was used instead of the dispersion.
[0209] (Example 7)
[0210] (1) Preparation of insulating particles
[0211] The following monomer composition was placed in a 1000 mL separable flask equipped with a four-mouth detachable cover, a stirring blade, a three-way stopcock, a condenser, and a temperature probe. After that, distilled water was added to make the solid content of the following monomer composition 10% by weight, stirred at 200 rpm, and polymerized at 60 ° C for 24 hours under a nitrogen atmosphere. The monomer composition contains 360 mmol methyl methacrylate, 45 mmol glycidyl methacrylate, 20 mmol p-phenylenediethylphosphine, 13 mmol ethylene glycol dimethacrylate, 0.5 mmol polyvinylpyrrolidone, and 1 mmol of 2,2'-azobis{2-[N-(2-carboxyethyl)amidino]propane}. After the reaction was completed, freeze-dried to obtain insulating particles (particle size 360 nm) having phosphorus atoms from p-phenylenediethylphosphine on the surface.
[0212] (2) Preparation of Conductive Particles with Insulating Particles
[0213] Conductive particles obtained in Example 6 were prepared. The insulating particles obtained were dispersed in distilled water under ultrasonic irradiation to obtain a 10 wt% aqueous dispersion of insulating particles. 10 g of the prepared conductive particles were dispersed in 500 mL of distilled water, 1 g of a 10 wt% aqueous dispersion of insulating particles was added, and stirred at room temperature for 8 hours. After filtering with a 3 μm mesh filter, the mixture was further washed with methanol and dried to obtain conductive particles with insulating particles attached. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the conductive particles with insulating particles attached were used instead of the conductive particles.
[0214] (Example 8)
[0215] Prepare polystyrene particles with an average particle size of 0.93 μm as seed particles. Mix 3.9 parts by weight of the polystyrene particles, 500 parts by weight of ion exchange water, and 120 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol to prepare a mixed solution. Disperse the mixed solution by ultrasonic wave, add it to a separable flask, and stir it evenly.
[0216] Next, 2 parts by weight of 2,2'-azobis(methyl isobutyrate) ("V-601" manufactured by Wako Pure Chemical Industries, Ltd.) and 2 parts by weight of benzoyl peroxide ("NYPER BW" manufactured by NOF Corporation) were mixed. 120 parts by weight of isoborneol diacrylate, 30 parts by weight of styrene, 9 parts by weight of triethanolamine lauryl sulfate, 30 parts by weight of ethanol, and 1,100 parts by weight of ion-exchanged water were further added to prepare an emulsion.
[0217] The emulsion was added to the mixed solution in the separable flask in several portions, and the mixture was stirred for 12 hours to allow the monomer to be absorbed by the seed particles, thereby obtaining a suspension containing the seed particles swollen with the monomer.
[0218] Then, 490 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol was added, heating was started, and the mixture was reacted at 85° C. for 9 hours to obtain resin particles.
[0219] Conductive particles, a conductive material, and a bonded structure were obtained in the same manner as in Example 1 except that the obtained resin particles were used.
[0220] (Example 9)
[0221] When preparing the resin particles, 2.34 parts by weight of 1,4-phenylenediamine was used instead of 4.25 parts by weight of 4,4′-diaminodiphenylmethane. Resin particles, conductive particles, a conductive material, and a bonded structure were obtained in the same manner as in Example 1 except for the above changes.
[0222] (Example 10)
[0223] When preparing the resin particles, 8.90 parts by weight of 2,2-bis[4-(4-aminophenoxy)phenyl]propane was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. Resin particles, conductive particles, a conductive material, and a bonded structure were obtained in the same manner as in Example 1 except for the above changes.
[0224] (Example 11)
[0225] When preparing the resin particles, 0.80 parts by weight of norbornanediamine was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. In addition, stirring at 68°C for 1 hour was changed to stirring at 45°C for 1 hour. In addition, the reaction conditions of 68°C and 20 hours were changed to reaction conditions of 45°C and 20 hours. Except for the above changes, resin particles, conductive particles, conductive materials and connected structures were obtained in the same manner as in Example 1.
[0226] (Comparative Example 1)
[0227] As seed particles, polystyrene particles with an average particle size of 0.93 μm were prepared. 3.9 parts by weight of the polystyrene particles, 500 parts by weight of ion exchange water, and 120 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol were mixed to prepare a mixed solution. The mixed solution was dispersed by ultrasonic wave, added to a separable flask, and stirred uniformly.
[0228] Next, 2 parts by weight of 2,2′-azobis(methyl isobutyrate) (“V-601” manufactured by Wako Pure Chemical Industries, Ltd.) and 2 parts by weight of benzoyl peroxide (“NYPER BW” manufactured by NOF Corporation) were mixed, and further 150 parts by weight of divinylbenzene, 9 parts by weight of triethanolamine lauryl sulfate, 30 parts by weight of ethanol, and 1,100 parts by weight of ion-exchanged water were added to prepare an emulsion.
[0229] The emulsion was added to the mixed solution in the separable flask in several portions, and the mixture was stirred for 12 hours to allow the seed particles to absorb the monomer, thereby obtaining a suspension containing the seed particles swollen with the monomer.
[0230] Then, 490 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol was added, heating was started, and the mixture was reacted at 85° C. for 9 hours to obtain resin particles.
[0231] Conductive particles, a conductive material, and a bonded structure were obtained in the same manner as in Example 1 except that the obtained resin particles were used.
[0232] (Comparative Example 2)
[0233] Conductive particles, a conductive material, and a bonded structure were obtained in the same manner as in Comparative Example 1, except that 30 parts by weight of 1,6-hexanediol dimethacrylate and 120 parts by weight of styrene were used instead of 150 parts by weight of divinylbenzene.
[0234] (Comparative Example 3)
[0235] As resin particles, "OPTBEADS 3500M" manufactured by Nissan Chemical Co., Ltd. was prepared. Conductive particles, a conductive material, and a bonded structure were obtained in the same manner as in Example 1 except that the prepared resin particles were used.
[0236] (evaluate)
[0237] (1) Particle size of resin particles (number average particle size) and CV value of particle size of resin particles
[0238] The particle sizes of about 100,000 resin particles were measured using a particle size distribution analyzer (Multisizer 4 manufactured by Beckman Coulter) to calculate the average value. The CV value of the particle size of the resin particles was calculated from the measured results of the particle size of the resin particles by the following formula.
[0239] CV value (%) = (ρ / Dn) × 100
[0240] ρ: Standard deviation of the particle size of the resin particles
[0241] Dn: average particle size of resin particles
[0242] (2) Aspect ratio of resin particles
[0243] The obtained resin particles were observed with an electron microscope to determine the aspect ratio. The aspect ratio was the average of the aspect ratios of 50 arbitrary resin particles.
[0244] (3) Shape of resin particles after compression release
[0245] Prepare the first plate and the second plate made of glass. The first plate and the second plate each have a flat surface. At the end of the surface of the first plate, a polyimide film having a thickness of 70% of the particle size of the resin particles is attached as a spacer material. After heating so that the surface temperature of the first plate and the second plate is 200°C, the obtained resin particles are arranged on the surface of the heated first plate. Within 3 minutes or more and 5 minutes after the resin particles are arranged, use a Wanli digital hot press ("MNP2-002D" manufactured by AS ONE) to move the first plate or the second plate to a position where the distance between the first plate and the second plate is 70% of the particle size (number average particle size) of the resin particles. That is, the resin particles are compressed by 30% in terms of particle size (number average particle size). The compression conditions are set to a compression speed of 2000mN / second and a load of 20000mN. The resin particles were compressed by 30% and held at 200°C for 10 minutes under a load of 20,000 mN, and then released from compression. The released resin particles were left at 25°C for 1 hour in a windless condition, and then photographed using an electron microscope.
[0246] Based on the obtained microscopic photograph, it is confirmed whether the resin particles after compression release viewed from a direction perpendicular to the compression direction have two planar portions facing each other in the compression direction.
[0247] In addition, when the distance between one end and the other end of the resin particle after compression is released is set to X, the ratio of the major diameter (A) of the resin particle after compression is released at a position of 0.05X from the one end toward the other end to the major diameter (B) of the resin particle after compression is released at a position of 0.5X from the one end toward the other end (major diameter (A) / major diameter (B)) is calculated. It should be noted that as the ratio (major diameter (A) / major diameter (B)), the average value of the ratio (major diameter (A) / major diameter (B)) of any 50 resin particles is used.
[0248] (4) Thermal decomposition temperature
[0249] The thermal decomposition temperature of the obtained resin particles was measured using a differential thermogravimetric simultaneous measuring apparatus ("TG / DTA: STA7200" manufactured by Hitachi High Tech Science Co., Ltd.). The thermal decomposition temperature is the temperature at which the weight of 10 mg of the resin particles is reduced by 10% when the temperature is increased at a rate of 5°C / min in air.
[0250] (5) 10% K value and 30% K value
[0251] The compression modulus (10% K value) and compression modulus (30% K value) of the obtained resin particles when compressed by 10% and compression modulus (10% K value) and compression modulus (30% K value) of the obtained conductive particles when compressed by 10% and compression modulus (30% K value) were measured by the above method. It should be noted that as a micro compression tester, "Fisher scope H-100" manufactured by Fisher was used.
[0252] (6) Thickness of the conductive part
[0253] The obtained conductive particles were added to "Technovit 4000" manufactured by Kulzer Co., Ltd., and dispersed so that the content of the obtained conductive particles was 30% by weight, thereby preparing an embedding resin body for inspection. The cross section of the conductive particles was cut out using an ion milling device ("IM4000" manufactured by Hitachi High Technologies Co., Ltd.) in a manner passing through the vicinity of the center of the conductive particles dispersed in the embedding resin body for inspection.
[0254] Furthermore, using a field emission transmission electron microscope (FE-TEM) (JEM-ARM200F manufactured by JEOL Ltd.), the image magnification was set to 50,000 times, 50 conductive particles were randomly selected, and the conductive portion of each conductive particle was observed. The thickness of the conductive portion in each conductive particle was measured, and the arithmetic average was processed as the thickness of the conductive portion.
[0255] (7) Adhesion between resin particles and conductive parts
[0256] The obtained connection structure was observed for the conductive particles in the connection portion using a scanning electron microscope ("Regulus 8220" manufactured by Hitachi High Technologies). For the 100 conductive particles observed, it was confirmed whether the conductive portion arranged on the surface of the resin particle was peeled off. The adhesion between the resin particle and the conductive portion was determined based on the following criteria.
[0257] [Criteria for Determining Adhesion Between Resin Particles and Conductive Part]
[0258] ○○○: The number of conductive particles whose conductive portion was peeled off was 0
[0259] ○○: The number of conductive particles from which the conductive portion was peeled is more than 0 and 15 or less
[0260] ○: The number of conductive particles from which the conductive portion was peeled was more than 15 and less than 30
[0261] △: The number of conductive particles whose conductive portion was peeled off was more than 30 and less than 50
[0262] ×: More than 50 conductive particles have been peeled off from the conductive portion
[0263] (8) Shape retention properties of conductive particles
[0264] The obtained connection structure was observed for the conductive particles in the connection portion using a scanning electron microscope ("Regulus 8220" manufactured by Hitachi High Technologies). The 100 conductive particles observed were checked to see whether the compressed shape was maintained. The shape retention property of the conductive particles was determined based on the following criteria.
[0265] [Criteria for Determining Shape Retention Characteristics of Conductive Particles]
[0266] ○○○: The number of conductive particles maintaining the compressed shape is 90 or more
[0267] ○○: The number of conductive particles that maintain a compressed shape is 70 or more and less than 90
[0268] ○: The number of conductive particles that maintain the compressed shape is 50 or more and less than 70
[0269] △: The number of conductive particles that maintain a compressed shape is 1 or more and less than 50
[0270] ×: The conductive particles do not maintain the compressed shape or the conductive particles are broken.
[0271] (9) Connection reliability (between upper and lower electrodes)
[0272] The connection resistance between the 20 upper and lower electrodes of the obtained connection structure was measured by the 4-terminal method. The average value of the connection resistance was calculated. It should be noted that, according to the relationship of voltage = current × resistance, the connection resistance can be obtained by measuring the voltage when a certain current flows. The connection reliability is determined according to the following criteria.
[0273] [Criteria for determining connection reliability]
[0274] ○○○: The average value of the connection resistance is 1.5Ω or less
[0275] ○○: The average value of the connection resistance is more than 1.5Ω and less than 2.0Ω
[0276] ○: The average value of the connection resistance is more than 2.0Ω and less than 5.0Ω
[0277] △: The average value of the connection resistance is more than 5.0Ω and less than 10Ω
[0278] ×: The average value of the connection resistance exceeds 10Ω
[0279] (10) Impact resistance
[0280] Twenty of the obtained connected structures were dropped from a height of 70 cm, and the impact resistance was evaluated by confirming the connection resistance in the same manner as the evaluation in (9). The impact resistance was determined based on the following criteria based on the rate of increase in the resistance value compared to the average value of the connection resistance obtained in the evaluation in (9).
[0281] [Impact resistance criteria]
[0282] ○: The increase rate of the resistance value compared to the average value of the connection resistance is 30% or less
[0283] △: The rate of increase in resistance compared to the average value of connection resistance is more than 30% and less than 50%
[0284] ×: The resistance value increased by more than 50% compared to the average value of the connection resistance
[0285] (11) Connection reliability under high temperature and high humidity conditions
[0286] 100 of the obtained connection structures were left at 85°C and 85% RH for 100 hours. The 100 connection structures after leaving were evaluated for whether or not conduction failure occurred between the upper and lower electrodes. The connection reliability after high temperature and high humidity conditions was determined based on the following criteria.
[0287] [Criteria for determining connection reliability after high temperature and high humidity conditions]
[0288] ○○: Among 100 connection structures, the number of connection failures is 1 or less
[0289] ○: Among 100 connection structures, the number of connection failures is 2 or more and 5 or less
[0290] △: Among 100 connection structures, the number of poor conduction is 6 or more and 10 or less
[0291] ×: Among 100 connection structures, 11 or more connection structures had poor conduction.
[0292] The results are shown in Tables 1 and 2. It should be noted that in Examples 1 to 7 and 9 to 11, the same Figure 8 (b) Similar electron microscope photo. In addition, Fig. 9 This is an electron microscope photograph of the resin particles in Example 8 after the compression was released. Fig.10 (a) is an electron microscope photograph of the resin particles after the compression was released in Comparative Example 1, Fig.10 (b) is an electron microscope photograph of the resin particles after the compression was released in Comparative Example 2, Fig.10 (c) is an electron micrograph of the resin particles in Comparative Example 3 after the compression was released.
[0293]
[0294]
[0295] Explanation of symbols
[0296] 1…Resin particles
[0297] 1a…1st surface (flat part)
[0298] 1b…Second surface (flat part)
[0299] 2…Conductive part
[0300] 11…Conductive particles
[0301] 21…Conductive particles
[0302] 22…Conductive part
[0303] 22A…1st conductive part
[0304] 22B…Second conductive part
[0305] 31…Conductive particles
[0306] 31a…protrusion
[0307] 32…Conductive part
[0308] 32a…protrusion
[0309] 33…Core material
[0310] 34…Insulating materials
[0311] 41…Connection structure
[0312] 42…First connection target component
[0313] 42a…1st electrode
[0314] 43…Second connecting object part
[0315] 43a…Second electrode
[0316] 44…Connection
[0317] 81…Electronic parts and devices
[0318] 82…No. 1 ceramic component
[0319] 83…Second ceramic component
[0320] 84…Joint
[0321] 84B…Glass
[0322] 85…Electronic components
[0323] 86…Lead frame
[0324] P…Compression direction
[0325] R…Interior Space
Claims
1. A resin particle, wherein The resin particles are held at 200° C. for 10 minutes in a state where the particle diameter is compressed by 30%, and then the compression is released. The distance between one end and the other end of the resin particles in the compression direction after the compression is released is defined as X. At this time, The ratio of the major diameter of the resin particle after the compression is released at a position of 0.05X from the one end toward the other end to the major diameter of the resin particle after the compression is released at a position of 0.5X from the one end toward the other end is in the range of 0.60 or more and less than 0.7, or in the range of greater than 0.85 and less than 0.95, The thermal decomposition temperature of the resin particles is 220°C to 300°C. The material of the resin particles contains epoxy resin, The epoxy resin is an epoxy resin selected from bisphenol A epoxy resin, bisphenol F epoxy resin, triazine epoxy resin, trifunctional glycidylamine epoxy resin and tetrafunctional glycidylamine epoxy resin.
2. The resin particle according to claim 1, wherein The compression modulus of the resin particles when compressed by 10% is 100 N / mm 2 Above 3500N / mm 2 the following.
3. The resin particles according to claim 1, wherein The compression modulus of the resin particles when compressed by 30% is 100 N / mm 2 Above 3000N / mm 2 the following. 4 . The resin particle according to claim 1 , which is used for a spacer, for an adhesive for electronic components, for obtaining conductive particles having a conductive portion, or for a laminate forming material. The resin particle according to any one of claims 1 to 3, which is used as a spacer for a liquid crystal display element, as an adhesive for electronic components, or for obtaining conductive particles having a conductive portion.
6. A conductive particle comprising: The resin particles according to any one of claims 1 to 5, and The conductive portion is disposed on the surface of the resin particle.
7. The conductive particle according to claim 6, wherein The compressive elastic modulus of the conductive particles when compressed by 30% is 4500 N / mm 2 Above 6000N / mm 2 the following.
8. The conductive particle according to claim 6 or 7, further comprising: An insulating material is disposed on the outer surface of the conductive portion.
9. The conductive particle according to claim 6 or 7, wherein The conductive portion has a protrusion on an outer surface.
10. A conductive material comprising: Conductive particles, and Binder resin, The said electroconductive particle has: the resin particle in any one of Claims 1-5, and the electroconductive part arrange|positioned on the surface of the said resin particle.
11. A connection structure comprising: 1st connection object component, a second connection target component, and a connecting portion connecting the first connection target member and the second connection target member, The connecting portion is formed of the resin particles according to any one of claims 1 to 5, or is formed of a composition containing the resin particles.
12. A connection structure comprising: a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connecting portion connecting the first connection target member and the second connection target member, The connecting portion is formed of conductive particles, or is formed of a conductive material containing the conductive particles and a binder resin. The conductive particle comprises: the resin particle according to any one of claims 1 to 5, and a conductive portion disposed on a surface of the resin particle. The first electrode and the second electrode are electrically connected via the conductive particles.
Citation Information
Patent Citations
Photosensitive composition, photospacer and method for producing photospacer, protective film, colored pattern, substrate for display device and display device
JP2009162871A
Resin particles, conductive particles, conductive material and connection structure
CN113614142A
Resin particles, conductive particles, conductive material, adhesive, connection structure and liquid crystal display element
WO2018230470A1